Positive Psychological States and Employee Creativity: The role of Ethical Leadership. (27th December 2018) - Younas, Amjad; Wang, Daoping; Javed, Basharat; Rawwas, Mohammed Y.A.; Abdullah, Iqra; Zaffar, Muhammad Adeel
Abstract: This study explores a new theoretical model of employee creativity by investigating the impact of ethical leadership on creativity mediated by creative self‐efficacy and psychological safety. Data collected from 200 supervisor–subordinate dyads in Pakistan reveal that ethical leadership is positively related to creativity. Further, psychological safety partially mediates the relationship between ethical leadership and creativity. However, creative self‐efficacy is found insignificant in the relationship between ethical leadership and creativity. The study discusses research and practical implications of the proposed new theoretical framework with regard to employee creativity.